2009
DOI: 10.1007/s00421-009-1099-1
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced elevation in plasma oxidative generating capability augments the temporal inflammatory response stimulated by lipopolysaccharide

Abstract: Prolonged oxidative stress is detrimental to health; however, transient oxidative stress may improve immune capability. We examined whether exercise-induced increases in the plasma oxidative generating capability enhance immune responsiveness to potential pathogens. Twelve individuals underwent a 30-min row and pre and post-exercise bloods were collected for oxidative stress and immune assessment. We found that exercise induced a transient increase in plasma carbonyls (3.2-5.3 nmol/mg protein) and creatine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Hydrolysed carboxy-dihydro-2′,7′-dichlorohydrofluorescein diacetate (carboxy-H 2 DCFDA, Merck, Ltd., Palmerston North, New Zealand) was used to assess the ROS-generating capacity of plasma, using a method previously described by Hurst et al [26]. Briefly, dihydro-2′,7′-dichlorohydrofluorescein (DCF), which is fluorescent when oxidised was added to diluted (1:4) plasma collected pre and post damage at 12, 36 and 60 hours in phosphate buffered saline [PBS], pH 7.4, Invitrogen NZ Ltd., Auckland, New Zealand), or PBS control, then 0.25 μM H 2 O 2 was added and the changes in fluorescence measured over 1600 s at 22°C using a fluorescence plate reader (BMG FluorStar Optima, Alphatech Systems Ltd, Auckland, New Zealand) with excitation and emission wavelengths of 485 and 520 nm respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrolysed carboxy-dihydro-2′,7′-dichlorohydrofluorescein diacetate (carboxy-H 2 DCFDA, Merck, Ltd., Palmerston North, New Zealand) was used to assess the ROS-generating capacity of plasma, using a method previously described by Hurst et al [26]. Briefly, dihydro-2′,7′-dichlorohydrofluorescein (DCF), which is fluorescent when oxidised was added to diluted (1:4) plasma collected pre and post damage at 12, 36 and 60 hours in phosphate buffered saline [PBS], pH 7.4, Invitrogen NZ Ltd., Auckland, New Zealand), or PBS control, then 0.25 μM H 2 O 2 was added and the changes in fluorescence measured over 1600 s at 22°C using a fluorescence plate reader (BMG FluorStar Optima, Alphatech Systems Ltd, Auckland, New Zealand) with excitation and emission wavelengths of 485 and 520 nm respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were randomly assigned to either the PLA or BAE study arms (18 participants per treatment arm in total), by an independent Plant & Food Research employee using a random-number generating Microsoft software computer programme, and blinded from both trial participants and the trial coordinator. The study (Figure 1), involved blinded participants consuming 2 opaque vegetable capsules (with 100 mL water) that contained either BAE (3.2 mg/kg total anthocyanins) or PLA and then 1 h later performing a 30 min rowing exercise (using a Concept 2 rower) at 70% VO 2max , previously described by our group (41,46). Blood and saliva samples were taken at set periods before and after this timed nutrition-exercise trial.…”
Section: Trial Formatmentioning
confidence: 99%
“…Thirty-four healthy individuals (13 females, 21 males) aged between 25 and 58 years, with a mean age of 38 ± 11 years, completed the study, and were able to maintain their usual diet and exercise regime over the 5 weeks and reported no injury or illness. In addition, before the start of the study, all participants took part in an initial familiarization session [applying the protocol outlined in Lyall et al (39) and Hurst et al (46)] to optimize the rowing intensity required to evoke an oxidative stress after 30 min (indicated by post-exercise increases in plasma MDA and oxidative generating potential). All subjects recruited in this study showed an increase in these oxidative stress indices after a 30 min row and subjectively reported no adverse health effects or muscle pain or tenderness the following day.…”
Section: Subject Analysismentioning
confidence: 99%
“…Our preliminary data are therefore encouraging and in the near future we hope to be able to evaluate the benefits of fruits on stress and inflammation robustly using animal models of exercise. In humans, exercise can have benefits on the immune system including an ability to positively modulate the acute inflammatory response to a simulated bacterial infection [14]. Furthermore, appropriate fruit extract consumption may assist these health benefits.…”
Section: Effect Of Fruit On Muscle Functionmentioning
confidence: 99%